Research on Electromagnetic Transient Processes of Long Marshalling High-Speed Train Passing Articulated Split-Phase Region - Ke Huang; Zhigang Liu; Xin Li (IEEE Access)
When a long marshaling high-speed train (HST) with two raised pantographs passes an articulated split-phase region, there will be eight electromagnetic transient processes along with pantograph arcing. These transients cause over-voltage in the train body (TB), which can have a negative effect on the train’s electronic equipment. In view of this issue, this paper closely analyzes the different transient processes generated by an HST passing a split-phase region. The analysis focuses on identifying the root causes and influencing factors relating to each transient process, examining, in particular, the capacitive coupling between TB and overhead contact system and the capacitive coupling between TB and the neutral wire. The results of this analysis are then used to establish Bergeron mathematical models that can be used to derive and study the eight independent transient processes. This leads to the generation of more detailed models that can be used to accurately simulate the phenomenon according to different variables, such as the phase difference of feeders, with Electromagnetic Transients Program (EMTP) software. The analysis results demonstrate that the hazardous PH over-voltages and TB over-voltages are easily generated. This paper concludes by drawing upon the simulation results to discuss possible over-voltage suppression measures, such as phase and grounding optimization for the pantograph and TB.